2003
DOI: 10.1086/345833
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacoeconomic Evaluation of 7‐Valent Pneumococcal Conjugate Vaccine in Canada

Abstract: The objective of this study was to evaluate the projected health benefits, costs, and cost-effectiveness of pneumococcal conjugate vaccination for infants and children aged <5 years in Canada. A health state model incorporating incidence, vaccine efficacy, costs, and transitional probabilities for the health states (well, meningitis, bacteremia, otitis media, pneumonia, and death) was constructed for a 10-year time horizon. Implementation of a pneumococcal conjugate vaccine program in Canada for each annual bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
8

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 16 publications
0
32
0
8
Order By: Relevance
“…Based on the results of Black et al [13], efficacy was assumed to be 85.7% at the ages of 5-11 months and 93.9% at the ages of 12 months to 9 years. Vaccine effectiveness was assumed to decline 3% per year starting 5 years after the last dosage [11]. Vaccine effectiveness against IPD was calculated by multiplying the efficacy of the vaccine with the serotype coverage (the proportion of IPD causing isolates with serotypes covered by the vaccine in the Netherlands [21] for the age group 0-9 years).…”
Section: Updating the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of Black et al [13], efficacy was assumed to be 85.7% at the ages of 5-11 months and 93.9% at the ages of 12 months to 9 years. Vaccine effectiveness was assumed to decline 3% per year starting 5 years after the last dosage [11]. Vaccine effectiveness against IPD was calculated by multiplying the efficacy of the vaccine with the serotype coverage (the proportion of IPD causing isolates with serotypes covered by the vaccine in the Netherlands [21] for the age group 0-9 years).…”
Section: Updating the Modelmentioning
confidence: 99%
“…In Western Europe, it is estimated that every child experiences one or more episodes of otitis media before the age of 2 years [7,8]. A number of studies have assessed the potential economical impact of mass infant vaccination with PCV7 (Prevnar; Wyeth) [9][10][11][12], since the first published clinical trial showed the high efficacy of this vaccine in the prevention of IPD [13] (see also McIntosh [14] for a recent review). Additionally, ongoing research has provided important new data.…”
Section: Introductionmentioning
confidence: 99%
“…Cost-effectiveness studies evaluating the pneumococcal conjugate vaccine in North America, Australia, and Europe suggest that it may be an efficacious and cost-effective strategy for reducing the health and economic burden of pneumococcal disease (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). While there is little doubt about the impact that this vaccine may have on health and health care in these countries, there is less agreement about whether this vaccine represents "good value for money" in low-and middle-income countries.…”
mentioning
confidence: 99%
“…16,39 More recent studies conducted in Australia, France, Canada, Germany and the United Kingdom revealed that the cost-benefit ratio of large scale vaccination is much higher, taking into account the impact on non-vaccinated persons. [46][47][48][49] In Australia, a variation in the rate of pneumococcal disease of 297 to 2,000/100,000 children under the age of 2 years was observed, depending on the population analyzed; the cost per year of life saved with the use of Pnc7 vaccine was calculated to be 190,000 Australian dollars, and by DALY, 104,000 Australian dollars. 46 In comparison with other regions of the world, however, the mortality rate from pneumococcal disease is low in Australia.…”
Section: Cost-effectiveness Of Pnc7 Vaccinementioning
confidence: 99%